2008
DOI: 10.1377/hlthaff.27.3.w242
|View full text |Cite
|
Sign up to set email alerts
|

How Risky Is Individual Health Insurance?

Abstract: This paper describes the relationship between type of insurance coverage in one period and the likelihood of becoming uninsured in the next. We find that for people at the median health status, becoming uninsured is most likely for those with individual insurance, less likely for those with small-group insurance, and least likely for those with largegroup insurance. However, for people in poor or fair health, the chances of losing coverage are much greater for people who had small-group insurance than for thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…There are various possibilities for alleviating such adverse effects (including guaranteed renewability), but these do not always exist, and the costs can be high. One American study found people in poor to fair health to be more likely to lose insurance coverage, particularly if they were in the small group market (Pauly and Lieberthal 2008). In the United States, a small fraction of those with preexisting conditions could get coverage (albeit often limited and expensive) through state high-risk pools.…”
Section: Potentially Catastrophically Expensive Services Tomentioning
confidence: 99%
“…There are various possibilities for alleviating such adverse effects (including guaranteed renewability), but these do not always exist, and the costs can be high. One American study found people in poor to fair health to be more likely to lose insurance coverage, particularly if they were in the small group market (Pauly and Lieberthal 2008). In the United States, a small fraction of those with preexisting conditions could get coverage (albeit often limited and expensive) through state high-risk pools.…”
Section: Potentially Catastrophically Expensive Services Tomentioning
confidence: 99%
“…19 In contrast, buyers of group insurance who are or become high risk and lose their employment for any reason have no protection against the reclassification risk that will occur if they move to individual insurance. 20 Neither option is superior to the other.…”
Section: Risk Segmentation and Help For High Risksmentioning
confidence: 99%
“…Uncertainty is also greater on the individual market; it is more likely for a person with an individual plan to lose insurance than someone under a group plan [27].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%